2019
DOI: 10.1007/978-981-13-6031-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Solution Probability Acceptance Within the Flower Pollination Algorithm for Combinatorial t-Way Test Suite Generation

Abstract: Flower Pollination Algorithm (FPA) is the new breed of metaheuristic for general optimization problem. In this paper, an improved algorithm based on Flower Pollination Algorithm (FPA), called imFPA, has been proposed. In imFPA, the static selection probability is replaced by the dynamic solution selection probability in order to enhance the diversification and intensification of the overall search process. Experimental adoptions on combinatorial tway test suite generation problem (where t indicates the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The computational comparison between the firefly meta-heuristic algorithm, genetic algorithm, and ant colony optimization revealed that the firefly algorithm has a shorter optimization time. Other models developed for solving combinatorial software testing using meta-heuristic searching include the memetic algorithm (MA) in [19], the particle swarm optimization (PSO) in [20], the artificial bee colony (ABC) and corresponding developed variants in [13], [21]- [26], the harmony search algorithm (HSA) in [27], the bat algorithm (BA) in [12], [28]- [30], and the flower pollination algorithm (FPA) in [31] and [32]. All these models are considered pure models because they utilize a common pure meta-heuristic approach.…”
Section: A Csst Testingmentioning
confidence: 99%
“…The computational comparison between the firefly meta-heuristic algorithm, genetic algorithm, and ant colony optimization revealed that the firefly algorithm has a shorter optimization time. Other models developed for solving combinatorial software testing using meta-heuristic searching include the memetic algorithm (MA) in [19], the particle swarm optimization (PSO) in [20], the artificial bee colony (ABC) and corresponding developed variants in [13], [21]- [26], the harmony search algorithm (HSA) in [27], the bat algorithm (BA) in [12], [28]- [30], and the flower pollination algorithm (FPA) in [31] and [32]. All these models are considered pure models because they utilize a common pure meta-heuristic approach.…”
Section: A Csst Testingmentioning
confidence: 99%